Transformation of Education Management in Supporting The Implementation of The Independent Curriculum in Indonesia - Albab, Ulul; Sunarni, Sunarni (Proceedings Series of Educational Studies, 2025)
Transformation of education management is an urgent need in facing global changes and internal challenges of the education system in Indonesia. The Independent Curriculum initiated by the Ministry of Education, Culture, Research, and Technology aims to provide flexibility in the learning process, emphasize competency, and accommodate technological developments and community needs. This article discusses the transformation of education management in supporting the implementation of the Independent Curriculum in Indonesia. The main focus of the discussion includes changes in the paradigm of school management, strengthening the role of the principal, and strategies for managing human resources and educational infrastructure. This study uses a qualitative approach with a case study method in several schools in Indonesia that have implemented the Independent Curriculum. The results of the study show that the transformation of education management has a crucial role in the successful implementation of the Independent Curriculum, especially in terms of principal leadership, teacher competency development, technology utilization, and competency-based learning evaluation